ANIMAL BONES AS TOOLS FROM ARCHAEOLOGICAL SITE VLINEVES, REGION MELNIK - UNETIC CULTURAL PERIOD (CZECH REPUBLIK) - Babić, Krešimir; Brnić, Željko; Mihelić, Damir Trbojević Vukičević, Tajana; Hincak, Zdravka (2003)
Protecting excavations on archaeological site Vlinĕ ves, region Mĕ lnik, near Praha, began in 2000. Abundant of animal osteological material was found in waste pits. After preparing for taxonomic analysis, the fragments, which were prepared in different tools, were separated. The most dominant bone fragments are those of red deer. Thus, ulna and metapodial bones were prepared in ovils, burr of antlers in hammers or hoes, ribs in palette knives and mandibulae in scrapers for raw leather dressing
Projekt MZOS
ENG